Great power multilateralism and the prevention of war debating a 21st century concert of powers - Müller, Harald 1949; Rauch, Carsten (New international relations, 2018)
Introduction : risks of great power conflict in the 21st century / Harald Müller, Carsten Rauch and Iris Wurm -- The concert of Europe and international security governance : how did it operate, what did it accomplish, what were its shortcomings, what can we learn? / Matthias Schulz -- Concerts as a mode of ordering in world politics : an ideal type approach / Adam Humphreys -- The dark side of the European concert of powers : caveats to be taken into account for successfully managing peace / Andreas Fahrmeir -- The dangers of great power connivance / Bertrand Badie -- The club practices of concert diplomacy : the paradox and effects of selective cooperation with global objectives / Mélanie Albaret and Delphine Lagrange -- The concert and existing organizations and legal structures at the global level / Stefan Kadelbach -- The normative foundations for a new global concert in an age of western retrenchment / Kyle Lascurettes and Sara B. Moller -- The concert of powers and competing government models / Hans-Joachim Spanger -- Just a concert or a just concert : the role of justice and fairness considerations / Harald Müller, Daniel Müller and Carsten Rauch -- The exclusion problem and the need for legitimacy / Konstanze J©ơngling and Siddharth Mallavarapu -- Ownership matters in a 21st century concert of powers / Pang Zhongying and Mao Weizhun -- Between informality and formality : concert operations in a densely institutionalized world / Kanti Bajpai and Harald Müller -- Concert of concerts : the geopolitical role of regional inter-state organizations / Alexander Nikitin and Oleg Demidov -- Great power accommodation, nuclear weapons and concerts of power / Nicola Leveringhaus and Andrew Hurrell -- Managing power transitions with a concert of powers / Harald Müller and Carsten Rauch